2001
DOI: 10.1046/j.1523-1747.2001.01327.x
|View full text |Cite
|
Sign up to set email alerts
|

Keratins and the Keratinocyte Activation Cycle

Abstract: In wound healing and many pathologic conditions, keratinocytes become activated: they turn into migratory, hyperproliferative cells that produce and secrete extracellular matrix components and signaling polypeptides. At the same time, their cytoskeleton is also altered by the production of specific keratin proteins. These changes are orchestrated by growth factors, chemokines, and cytokines produced by keratinocytes and other cutaneous cell types. The responding intracellular signaling pathways activate transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
396
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 487 publications
(429 citation statements)
references
References 156 publications
19
396
0
3
Order By: Relevance
“…Paradoxically, Alevizos et al (2001) using oligonucleotide array reported a low expression of keratins 4 and 15 in HNSC. Our results are also supported by previous investigations of head and neck and other mucosa-derived squamous carcinomas in which upregulation of basal and proliferation-induced keratins were found (Freedberg et al, 2001;Mischke, 1998). The collective results suggest a potential diagnostic and biologic role for keratin expression in these tumors (Balm et al, 1996;Chu et al, 2001;Heyden et al, 1992;Ivanyi et al, 1990;Klijanienko et al, 1993;Mischke, 1998;Ogden et al, 1993).…”
Section: Discussionsupporting
confidence: 92%
“…Paradoxically, Alevizos et al (2001) using oligonucleotide array reported a low expression of keratins 4 and 15 in HNSC. Our results are also supported by previous investigations of head and neck and other mucosa-derived squamous carcinomas in which upregulation of basal and proliferation-induced keratins were found (Freedberg et al, 2001;Mischke, 1998). The collective results suggest a potential diagnostic and biologic role for keratin expression in these tumors (Balm et al, 1996;Chu et al, 2001;Heyden et al, 1992;Ivanyi et al, 1990;Klijanienko et al, 1993;Mischke, 1998;Ogden et al, 1993).…”
Section: Discussionsupporting
confidence: 92%
“…The percentage of the total TGF-β activation (± SEM) was defined using an anti-TGF-β neutralizing antibody. *P < 0.05; **P < 0.001. link innate immune responses to subsequent adaptive immune responses, ultimately promoting wound repair (50). Thus, the induction of IL-1β that occurs during SM of the airway epithelium may act as both an autocrine factor to influence gene expression to facilitate cell migration and wound closure and as a paracrine factor to recruit inflammatory cells and to induce matrix production and contractility of adjacent fibroblasts (51,52).…”
Section: Figurementioning
confidence: 99%
“…Upon injury, keratinocytes are the first cells that respond (6,7) by releasing pre-stored interleukin-1 (IL-1) (8). IL-1 has an autocrine and a paracrine function; that is, to activate keratinocytes and to alert the surrounding cells and tissues.…”
mentioning
confidence: 99%
“…The release of IL-1 by keratinocytes, with subsequent release of additional signaling molecules (9,10), demarcates the proinflammatory phase of wound healing. In response to these signals, activated keratinocytes start migrating and proliferating (7,8,11). Successful repair after tissue injury requires resolution of inflammatory response, transitioning keratinocyte (HEK) from activated to differentiating phenotype.…”
mentioning
confidence: 99%